Cognitive Impairment Impacts Exercise Effects on Cognition in Multiple Sclerosis - Rademacher, Annette; Joisten, Niklas; Proschinger, Sebastian; Bloch, Wilhelm; Gonzenbach, Roman; Kool, Jan; Langdon, Dawn; Bansi, Jens; Zimmer, Philipp (Frontiers in Neurology, 2021)
Abstract Purpose Exercise training reveals high potential to beneficially impact cognitive performance in persons with Multiple Sclerosis (pwMS). Research indicates that high intensity interval training (HIIT) has potentially higher effects on physical fitness and cognition compared to moderate continuous exercise. This study compares i) the effects of a three- week HIIT and moderate continuous exercise training on cognitive performance and cardiorespiratory fitness of pwMS in an overall analysis and ii) investigates potential effects based on baseline cognitive status in a subgroup analysis. Methods 75 pwMS were randomly assigned to an intervention (HIIT: 5x 1.5min intervals at 95-100% HRmax, 3x/week) or active control group (CG: 24min continuous exercise at 65% HRmax, 3x/week). Cognitive performance was assessed pre and post intervention with the Brief International Cognitive Assessment for MS (BICAMS). I) To examine potential within (time) and interaction (time x group) effects in the overall analysis, separate analyses of covariance (ANCOVA) were conducted. II) For the subgroup analysis, participants were divided into two groups (intact cognition or impaired cognition (> 1.5 standard deviation (SD) compared to healthy, age-matched norm data in at least one of the three tests of the BICAMS). Potential impacts of cognitive status and intervention were investigated with multivariate analyses of variance (MANOVA). Results Overall analysis revealed significant time effects for processing speed, and verbal learning, rel. VO2peak and rel. power output. A time*group interaction effect was observed for rel. power output. Subgroup analysis indicated a significant main effect for cognition (impaired cognition vs. intact cognition). Subsequent post-hoc analysis showed significant larger effects on verbal learning in pwMS with impaired cognition. Conclusion Current results need to be confirmed in a powered randomized controlled trial with cognitive performance as primary endpoint and eligibility based on cognitive performance that is assessed prior to study inclusion.